2003
DOI: 10.1007/s00586-003-0567-2
|View full text |Cite
|
Sign up to set email alerts
|

Routine primary care management of acute low back pain: adherence to clinical guidelines

Abstract: One of the major challenges for general practitioners is to manage individuals with acute low back pain appropriately to reduce the risk of chronicity. A prospective study was designed to assess the actual management of acute low back pain in one primary care setting and to determine whether existing practice patterns conform to published guidelines. Twenty-four family physicians from public primary care centers of the Basque Health Service in Bizkaia, Basque Country (Spain), participated in the study. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 29 publications
5
50
1
3
Order By: Relevance
“…Similar rates of patient-physician consultations for a new episode of neck pain (1-2% [11,22]) and LBP (2-4% [23,24]) have been reported from other countries. When comparing the results of this study to GP management which has been previously reported, our results suggest that Australian GPs deliver advice less often and refer patients more frequently for imaging.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Similar rates of patient-physician consultations for a new episode of neck pain (1-2% [11,22]) and LBP (2-4% [23,24]) have been reported from other countries. When comparing the results of this study to GP management which has been previously reported, our results suggest that Australian GPs deliver advice less often and refer patients more frequently for imaging.…”
Section: Discussionsupporting
confidence: 62%
“…When comparing the results of this study to GP management which has been previously reported, our results suggest that Australian GPs deliver advice less often and refer patients more frequently for imaging. Previous studies have reported that advice is delivered to up to 97% [11] of patients for new neck pain and to between 32 and 76% [23][24][25][26] for LBP. It is important to consider the method in which these data are collected as it can significantly alter the rates reported.…”
Section: Discussionmentioning
confidence: 99%
“…We used the 24-item RMDQ to measure pain-related disability, which includes items such as, "Because of my pain, I lie down to rest more often" [34][35]. The RMDQ has been used to evaluate patients with chronic pain and has shown internal consistency and validity [42][43]. Scores range from 0 to 24, with higher scores indicating more severe disability.…”
Section: Pain-related Clinical Characteristicsmentioning
confidence: 99%
“…In the absence of specific spinal pathology all the clinical practice guidelines (CPG) are unanimous in advising patients to keep active despite their pain, continue their ordinary activities and keep or return soon to work. However, there is evidence to suggest difficulties in the implementation and impact of guidelines on the practice of physiotherapists and practitioners [6][7][8]. One of the barriers which limit the adherence of physicians to CPG recommendations could be the beliefs and attitudes that they hold about LBP, beyond their specific knowledge of the recommended contents.…”
Section: Introductionmentioning
confidence: 99%